Proceedings of the Health Science International Conference (HSIC 2017) 2017
DOI: 10.2991/hsic-17.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Nursing Performance through Career Development

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Based on these results it can be explained that the higher the remuneration will affect the job satisfaction. This finding is in line with researches from Putra et al, (2017) proves that career development has a positive and significant effect on nurse job satisfaction. work goals have a positive and significant effect on the performance of nurses.…”
Section: Direct Effect Of Remuneration and Job Satisfactionsupporting
confidence: 92%
“…Based on these results it can be explained that the higher the remuneration will affect the job satisfaction. This finding is in line with researches from Putra et al, (2017) proves that career development has a positive and significant effect on nurse job satisfaction. work goals have a positive and significant effect on the performance of nurses.…”
Section: Direct Effect Of Remuneration and Job Satisfactionsupporting
confidence: 92%
“…Extant literature on employee satisfaction has shown that while its determinants may vary among different jobs, it has a crucial influence on worker's performance (Jalagat, 2016; Torlak & Kuzey, 2019). In the case of healthcare, nurse satisfaction is a consistent predictor of nursing performance and patient satisfaction (Ahmad et al., 2017; Perry et al., 2018; Putra et al., 2017). This link is also observed when using longitudinal data (Shazadi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%